The Impact of Spontaneous Labor Before Elective Repeat Cesarean Delivery on Pregnancy Outcome: A Prospective Cohort Study. Issue 4 (7th October 2021) - Ramadan, Mohamad K.; Jarjour, Ibtissam; Hubeish, Manal; Itani, Saad Eddine; Mneimneh, Sirin; Badr, Dominique A.
Abstract: Objective: To investigate the effects of spontaneous labor before elective repeat cesarean delivery (ERCD) on short-term maternal and neonatal outcomes. Methods: This was a prospective cohort study. All consecutive ERCDs, occurring at ≥37 weeks of gestation between July 1, 2017 and December 31, 2019 in Makassed General Hospital, were evaluated. The maternal and neonatal outcomes of 183 laboring women undergoing unscheduled repeat cesarean delivery (URCD) group were compared with those of 204 women undergoing cesarean delivery (CD) without spontaneous labor (ERCD) group. Primary outcomes were "composite adverse maternal outcome" and "composite adverse neonatal outcome." Fisher's exact and Student's t tests were used to assess the significance of differences in dichotomous and continuous variables, respectively. Two logistic regression models were constructed to identify risk factors with most significant influence on the rate of composite adverse maternal and neonatal outcomes. Results: "Composite adverse maternal outcome" was significantly more common in women who underwent spontaneous labor ((40/183) 21.9% vs . (19/204) 9.3%, P = 0.001, relative risk ( RR ): 2.7, 95% confidence interval ( CI ): 1.50–4.90). Similarly, "composite adverse neonatal outcome" was significantly increased in the URCD group ((24/183) 13.1% vs . (12/204) 5.9%, P = 0.014, RR : 2.4, 95% CI : 1.18–4.98). These adverse effects persisted after adjustment for confounders. Multivariate regression models revealed that, besides labor, CD-order impacted maternal outcome ( RR : 1.5, 95% CI : 1.02–2.30, P = 0.036), while CD-order and teenage pregnancy influenced neonatal outcome ( RR : 2.1, 95% CI : 1.29–3.38, P = 0.003, and RR : 16.5, 95% CI : 2.09–129.80, P = 0.008, respectively). Conclusion: In our study, spontaneous labor before ERCD, including deliveries at term, was associated with adverse maternal and neonatal outcomes, indicating that it is preferable to conduct ERCD before the onset of labor. Screening women with MRCD may identify those at increased risk for spontaneous labor for whom CD could be scheduled 1–2 weeks earlier. Further large prospective studies to assess the effects of such an approach on maternal and neonatal outcomes are strongly warranted.